Gender Inequality in the Divorce System: Taking Property Division as the Starting Point - Zhou, Xiaozhang (Transactions on Social Science, Education and Humanities Research, 2024)
Both the legislature and the public gradually realized the significance of divorce autonomy, which is thought to be the progress of the law-based society and shows the increasing awareness of protecting women’s rights. With the change from fault-based divorce to “no-fault” divorce, certain plight had been solved, providing people with more remedy approaches to get rid of painful marital relationships. However, statistics show that related provisions have not functioned well in the judicial practice. Regulatory research figured out that there existed a confusion of related issues in the divorce proceedings, which caused a new mode of inequality with modern features in the court. Which domestic violence is the one that needs the most attention as it involves a threat to life security. Therefore, verdicts of divorces involving domestic violence should be decisive, avoiding potential threat by the assaulter, and issues related to the divorce should be separately considered.